Challenges associated with the implementation of institutional quarantine and isolation strategies during major multicountry viral outbreaks in Africa (2000–2023): a scoping review - Amzat, Jimoh; Oduwole, Ebunoluwa; Lawal, Saheed Akinmayowa; Aluko-Arowolo, Olusola; Afolabi, Rotimi; Adedeji, Isaac Akinkunmi; Temisan, Ige Angela; Oludiran, Ayoyinka; Aminu, Kafayat; Salami, Afeez Abolarinwa; Kanmodi, Kehinde Kazeem (Global health research and policy, 2024)
Quarantine and isolation (Q&I) are interrelated but not mutually exclusive public health practices for disease control, which may face public resistance in the context of health emergencies due to associated challenges. Hence, it is often tough for most countries to implement Q&I even in the context of health emergencies. Therefore, this scoping review examines the challenges associated with the implementation of institutional Q&I strategies during major multicountry viral outbreaks (Ebola, Lassa and COVID-19) in Africa between 2000 and 2023. This scoping review was designed based on Arksey and O'Malley's guidelines. A systematic literature search, using nine online research databases, was conducted with the aid of relevant search terms, Boolean operators and truncations. All articles obtained from the literature search were electronically imported into Rayyan web application for deduplication based on specific inclusion and exclusion criteria. From the included literature, relevant data were charted, summarized, collated, and presented. This review included 24 of the 787 retrieved articles. Sixteen of the 24 selected articles investigated issues related to COVID-19 prevention and control in Africa. Two assessed precautionary practices for Lassa fever, while five were on Ebola virus disease. However, one article explored knowledge, preventive practices, and general isolation precautions. The review identified various challenges that hindered the implementation of successful Q&I practices during viral infection outbreaks in Africa. Essential healthcare infrastructure, equipment (medical supplies including personal protective equipment and testing kits) and facilities that are essential for Q&I were deficient. Q&I implementation was often threatened by low human resource capacity and inefficiencies in the healthcare system which portray Africa as unprepared to handle complex public health crises. This review shows that Q&I implementation in Africa is often threatened by low human resource capacity and inefficiencies in the healthcare system and also portrays Africa as unprepared to handle complex public health crises. Hence, Q&I for major multicountry outbreaks in Africa is very challenging. Therefore, continuous efforts to address these identified challenges are crucial to enhancing health emergency preparedness in Africa.